2023
DOI: 10.1172/jci159103
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical evidence for suppression of alcohol intake by apremilast

Abstract: Treatment options for Alcohol Use Disorders (AUD) have minimally advanced since 2004, while the annual deaths and economic toll have increased alarmingly. Phosphodiesterase type 4 (PDE4) is associated with alcohol and nicotine dependence. PDE4 inhibitors were identified as a potential AUD treatment using a novel bioinformatics approach. We prioritized a newer PDE4 inhibitor, apremilast, as ideal for repurposing, (i.e. FDA approved for psoriasis, low incidence of adverse events, excellent safety profile), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…In a randomized, double-blind, placebo-controlled trial, the phosphodiesterase inhibitor pentoxifylline associated with escitalopram showed greater reduction of depression scores compared to patients receiving escitalopram alone (27). In another study, Apremilast which is also a phosphodiesterase inhibitor, suppressed excessive alcohol drinking in AUD patients (28). Paraxanthine has a psychostimulant effect and can modulate dopamine release in the striatum (29).…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, double-blind, placebo-controlled trial, the phosphodiesterase inhibitor pentoxifylline associated with escitalopram showed greater reduction of depression scores compared to patients receiving escitalopram alone (27). In another study, Apremilast which is also a phosphodiesterase inhibitor, suppressed excessive alcohol drinking in AUD patients (28). Paraxanthine has a psychostimulant effect and can modulate dopamine release in the striatum (29).…”
Section: Discussionmentioning
confidence: 99%
“…A six‐week clinical trial that aims to replicate the effects on alcohol consumption is currently underway (NCT05414240). Apremilast, also a PDE inhibitor, a target dosage of 90 mg/day of apremilast, was recently shown to reduce the number of drinks/day and the proportion of heavy drinking days in an 11‐day trial in non‐treatment‐seeking individuals with AUD (Grigsby et al, 2023).…”
Section: Medications To Reduce or Stop Drinkingmentioning
confidence: 99%
“…Apremilast, also a PDE inhibitor, a target dosage of 90 mg/day of apremilast, was recently shown to reduce the number of drinks/day and the proportion of heavy drinking days in an 11-day trial in nontreatment-seeking individuals with AUD (Grigsby et al, 2023).…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…15 Currently, PDE4 inhibitors apremilast and ibudilast are undergoing clinical trials to treat AUD. 17,18 On the other hand, chronic alcohol consumption also resulted in the upregulation of hepatic PDE4 expression and the deficiency of cAMP signaling in hepatic tissues of patients, 19 and PDE4 inhibitor rolipram significantly reduced alcohol-induced hepatic steatosis and injury by reduced oxidative and endoplasmic reticulum stress. 19 These results indicate that PDE4 might serve as a novel target for both AUD and ALD treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many studies have confirmed that dysregulation of cAMP/PKA signaling has been implicated in the development of EtOH drinking behavior. , Moreover, intracellular signaling, mediated by secondary messenger cAMP, is an essential basis for genetic predisposition, reward characteristics, systemic toxicity, and relapse characteristics of compulsive alcohol consumption . Currently, PDE4 inhibitors apremilast and ibudilast are undergoing clinical trials to treat AUD. , On the other hand, chronic alcohol consumption also resulted in the up-regulation of hepatic PDE4 expression and the deficiency of cAMP signaling in hepatic tissues of patients, and PDE4 inhibitor rolipram significantly reduced alcohol-induced hepatic steatosis and injury by reduced oxidative and endoplasmic reticulum stress . These results indicate that PDE4 might serve as a novel target for both AUD and ALD treatment.…”
Section: Introductionmentioning
confidence: 99%